(untitled) (Praxis Educativa, 2014)
In the first part this paper describes a research about the identity of the Children’s Education Career. Beginner and future teachers of this education level have taken part in this investigation. They have answered two main questions: how they are learning to be teachers, and what kind of teachers they want to be. In the second part, this article presents the methodological problems, that emerged during the investigation connected with the vulnerability of the actors (researcher and investigated teachers) of these life histories.